Nexus between FDI, Financial Development, Capital Formation and Renewable Energy Consumption; evidence from Bangladesh - Kor, Sylvia; Qamruzzaman, Md (International Journal of Energy Economics and Policy, 2023)
This paper examines the interplay among foreign direct investment (FDI), financial development, capital formation, and renewable energy consumption in the context of Bangladesh. The study uses empirical evidence to shed light on the nexus between these variables. Panel data analysis techniques investigate the relationship over a specific period. This research provides insights into Bangladesh’s dynamic interactions among FDI, financial development, capital formation, and renewable energy consumption. The study reveals significant positive associations between FDI and renewable energy consumption, indicating that FDI inflows contribute to the growth and utilization of renewable energy sources. Moreover, the analysis uncovers a positive relationship between financial development and renewable energy consumption, suggesting that a well-developed financial sector facilitates the financing and implementation of renewable energy projects. Additionally, the study highlights the role of capital formation in promoting renewable energy consumption. The positive relationship between capital formation and renewable energy consumption indicates that investment in physical infrastructure and productive assets supports the expansion and utilization of renewable energy sources. This analysis provides empirical evidence of the interdependencies among FDI, financial development, capital formation, and renewable energy consumption in Bangladesh. Overall, the findings suggest that fostering FDI, improving financial sector development, and promoting capital formation are crucial for enhancing renewable energy consumption in Bangladesh. The study’s conclusions have implications for policymakers and stakeholders in designing and implementing strategies to promote sustainable and renewable energy sources in the country.